2011
DOI: 10.1021/jp206959k
|View full text |Cite
|
Sign up to set email alerts
|

CNT@Cu3(BTC)2 and Metal–Organic Frameworks for Separation of CO2/CH4 Mixture

Abstract: Effectively separating CO2 from the natural gas, which is one of alternative “friendly” fuels, is a very important issue. A hybrid material CNT@Cu3(BTC)2 has been prepared to separate CO2 from the CO2/CH4 mixture. For comparison of separation efficiency, a series of representative metal–organic frameworks (MOF-177, UMCM-1, ZIF-8, MIL-53 (Al), and Cu3(BTC)2) have also been synthesized by the solvothermal method. Adsorption isotherms of CO2 and CH4 pure gases are measured by Hiden Isochema Intelligent Gravimetri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
87
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(92 citation statements)
references
References 49 publications
(85 reference statements)
4
87
1
Order By: Relevance
“…48 At zero loading, Q st of CH 4 , C 2 H 6 and C 3 H 8 adsorption is 18, 25 and 44 kJ mol -1 , respectively, as estimated from the sorption isotherms at 273 and 298 K (Fig. [54][55][56] The potential application for the industrially important small hydrocarbon separation is also explored for JLU-Liu18 by IAST. It indicated that the unique cage structures of JLU-Liu18 with medium pore size induce stronger interaction with larger hydrocarbons than the smaller ones.…”
Section: Resultsmentioning
confidence: 99%
“…48 At zero loading, Q st of CH 4 , C 2 H 6 and C 3 H 8 adsorption is 18, 25 and 44 kJ mol -1 , respectively, as estimated from the sorption isotherms at 273 and 298 K (Fig. [54][55][56] The potential application for the industrially important small hydrocarbon separation is also explored for JLU-Liu18 by IAST. It indicated that the unique cage structures of JLU-Liu18 with medium pore size induce stronger interaction with larger hydrocarbons than the smaller ones.…”
Section: Resultsmentioning
confidence: 99%
“…[13][14][15][16] Yang et al 14 prepared carbon nanotube (CNT)/MOF-5 hybrid composite and found that the surface area and the hydrogen storage capacity were signicantly improved compared to pure MOF-5. Xiang et al 17 synthesized the CNT/ [Cu 3 (BTC) 2 ] hybrid via CNT incorporation. The CO 2 and CH 4 uptakes on this composite increased dramatically compared to the unmodied MOFs.…”
mentioning
confidence: 99%
“…However, dramatic mass losses, indicating the breakdown of the framework, were observed at 310–440°C, as shown in Figure . Xiang et al . reported the thermodynamic stability of Cu‐BTC and CNTs@Cu‐BTC up to 200°C.…”
Section: Resultsmentioning
confidence: 99%